This is Temporary : How transient projects are redefining architecture - St Hill, Cate (Newcastle upon Tyne : RIBA Publishing, 2016)
Gun Architects ; Public realm and engagement: facilitating possibilities and animating places ; We Made That ; The Decorators ; Party on: the political value of temporary ; Playful Storytellers: digging deeper and building narratives. Interviews: Aberrant Architecture (UK) / Studio Weave (UK) ; Aberrant Architecture ; Studio Weave ; Collectives and self-initiated projects: making it up as you go along. Interviews: Assemble (UK) / EXYZT (France and UK) / Practice Architecture (UK) ; Assemble ; EXYZT ; Practice Architecture ; Building Alternative Possible Worlds ; Participative building and materiality: scarcity of resources and a platform for communication. Interviews: Folke Köbberling and Martin Kaltwasser (Germany) / Plastique Fantastique (Germany) ; Köbberling / Kaltwasser ; Plastique Fantastique ; The art world and temporary architectue: the meeting of two disciplines. Interviews: GRUPPE (Switzerland) / Morag Myerscough (UK) ; GRUPPE ; Morag Myerscough ; Learning from canning town Caravanserai: a temporary town and its legacy
boek